Impact of digital finance on the performance of the stock market in Nigeria - Adepoju Adeoba Asaolu; Omolayo Joseph Oluwole; Mary Oluwayemisi Akosile (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2025)
This research analyses the influence of digital finance on the performance of the Nigerian stock market from 2009 to 2023. This study examines the impact of Automated Teller Machine (ATM) transactions, Point of Sale (POS) transactions, mobile payment transactions, and online payment transactions on stock market capitalisation in Nigeria. The research employs an ex-post facto design and utilises secondary time series data obtained from the Central Bank of Nigeria Statistical Bulletin. Descriptive and inferential statistics, including multiple regression analysis, were employed to examine the data. The results demonstrate a robust and significant correlation between digital finance and stock market success. Web pay transactions have the most substantial positive impact on market capitalisation, indicating that online payment methods augment investor engagement and stock market expansion. Conversely, ATM and mobile payment transactions exhibit adverse effects, suggesting possible inefficiencies or restricted integration with stock market operations. POS transactions exhibit a modest yet favourable impact on stock market capitalisation. The research finds that digital finance is essential for advancing stock market growth in Nigeria. It advises that governments and financial institutions policy makers should deepen digital finance platforms with capital market services, augment infrastructure, and elevate digital literacy to optimise the advantages of digital finance for stock market performance.